CREATIVE STRATEGY IN PRODUCTION OF PROMOTION VIDEO FOR THE RATTAN TOURISM VILLAGE OF TRANGSAN - Morgana, Daniel Andhika; Rizal H, Sigit; Bilankawa, Firdana; Ramadhian, Alpin; Ardi Candra D.A, Nur Rahmat (Capture : Jurnal Seni Media Rekam, 2019)
One aspect that affects the speed of development of a tourist village is the promotion of the village. Promotion of village tourism is very important especially for villages that are pioneering. Village promotion can be carried out by internal elements who carry out promotions and information intensively. Therefore, it is necessary to involve the village youth group "Susilo Bhakti" of Trangsan Village. Research methods with a focus on creative strategies implemented in the preproduction, production and post-production stages. The results of the study showed that 1) village youth group were able to make creative videos that highlighted the uniqueness of the Rattan Tourism Village of Trangsan; 2) Strategy in the preproduction stage is to emphasize the importance in determining ideas and concepts that are the main theme, 3) Strategy in the production phase is to focus on understanding about the several types of shooting of local village tourism objects, and 4) Strategy in the post-production stage is focus on image editing and publication on social media Youtube and Instagram.